Comparison of intradermal injection of autologous epidermal cell suspension vs. spraying of these cells on dermabraded surface of skin of patients with post-burn hypopigmentation - Ahrari Iman; Mohamadi Ali Akbar; Khosravi Maharlooei Mohsen; Farsi Ali; Attar Armin; Ahrari Sajjad; Monabati Ahmad; Mahsa Ghavipisheh; Rahnama Leila (Wolters Kluwer Medknow Publications, 2013)
Introduction: One of the most important complications after burning is hypo/depigmentation. This study was designed to compare two methods of cell spray and intradermal injection of epidermal cell suspension for treatment of burn induced hypopigmentation. Material and Methods: In this study, 28 patients with post burn hypo/depigmentation were selected and divided in 2 groups. A small skin biopsy was taken from normal skin of patients in operation room and epidermal cell suspension was prepared using NaBr 4N and trypsin. In the first group, the epidermal cell suspension was sprayed on the wound surface and then the area was dressed with amniotic membrane and gauze. In the second group, the cell suspension was injected in intradermal manner in the hypopigmented area. The patients were followed up and to evaluate the effect of the cells, photos were taken from the area before operation and also at follow-up. Clinical evaluation was done by the surgeon and a clinical score between "0" to "4" was used to demonstrate the clinical status from poor to excellent pigmentation. Skin biopsies were taken from depigmented area before and after interventions. Melanocytes were stained using anti S100 antibody and were counted in ×400 magnification fields. Results: Eighteen patients were in cell spray and 10 were in cell injection groups. Mean change of pigmentation in two group showed that there was no statistical significant differences in pigmentation between two groups, (P value = 0.52) although a limited improvement in pigmentation status was observed in both groups. Regarding melanocyte numbers per field, there was not a significant difference between two groups and also before and after interventions, but melanocyte number increased after treatment in both groups. Conclusion: We did not find noticeable differences between cell spray and intradermal injection methods. Although both methods showed a limited effect on pigmentation of depigmented skin, the clinical results were not satisfactorily for both patients and clinicians.